2017
DOI: 10.3389/fnsys.2017.00052
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Dorsal and Ventral Striatum in the Sensitivity of Tonically Active Neurons to Rewarding Events

Abstract: Within the striatum, cholinergic interneurons, electrophysiologically identified as tonically active neurons (TANs), represent a relatively homogeneous group in terms of their functional properties. They display typical pause in tonic firing in response to rewarding events which are of crucial importance for reinforcement learning. These responses are uniformly distributed throughout the dorsal striatum (i.e., motor and associative striatum), but it is unknown, at least in monkeys, whether differences in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 57 publications
(79 reference statements)
1
28
1
Order By: Relevance
“…). The pause-pulse nature of TANs responses has become almost diagnostic for their identification (Marche et al, 2017) and is frequently used as one of the criteria to identify TANs. For at least some of the reward offerings each of our TANs showed the pause followed by an excitatory rebound response that has been taken as characteristic of TANs (Kimura et al, 1984(Kimura et al, , 1990Apicella, 2002Apicella, , 2017.…”
Section: 2001mentioning
confidence: 99%
See 2 more Smart Citations
“…). The pause-pulse nature of TANs responses has become almost diagnostic for their identification (Marche et al, 2017) and is frequently used as one of the criteria to identify TANs. For at least some of the reward offerings each of our TANs showed the pause followed by an excitatory rebound response that has been taken as characteristic of TANs (Kimura et al, 1984(Kimura et al, , 1990Apicella, 2002Apicella, , 2017.…”
Section: 2001mentioning
confidence: 99%
“…At this point it is not clear whether the phase reversing responses we have seen are characteristic of TANs throughout the striatum, and they can only be seen when there is a wide range of values to encode, or whether they are found only in this limbic striatum. In monkeys the one study that compares TANs in the dorsal, intermediate, and ventral striatum shows that the dorsal and ventral TANs have differences in response latency and pause width in response to rewarding events (Marche et al, 2017), so it is at least plausible to think this could be a characteristic found only in limbic striatum, but it is possible that the reversing modulation we have seen in ventral TANs is also a feature of dorsal TANs response, if they were to be recorded under the same experimental circumstances.…”
Section: 2001mentioning
confidence: 99%
See 1 more Smart Citation
“…. The responsive TANs were mainly located in the dorsolateral region of the putamen and in the region that is posterior to the anterior commissure; these areas correspond to known sensorimotor areas of the putamen (Parent & Hazrati, ; Haber, ; Marche et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…These findings dovetail with the notion that the ventral striatum computes the value of the stimulus ('critic') while the dorsal striatum plays a role in selecting an action/response ('actor') 50 . Several empirical studies provided supportive evidence for the idea but were all limited to extrinsic incentives 51,52,65 . Our findings suggest that 21 the neural computation of curiosity-based decision-making can possibly be understood within the actor-critic model of reinforcement learning.…”
Section: Discussionmentioning
confidence: 99%